Silver incorporation into gold patchy nanoparticles: Influence on the tunability and long-term stability of plasmonic properties - Seifert, Julia; Traore, Nabi; Diesch, Joshua; Kichigin, Aleksandr; Nees, Nico; Peukert, Wolfgang; Spiecker, Erdmann; Apeleo Zubiri, Benjamin; Pflug, Lukas; Klupp Taylor, Robin (Journal of Physical Chemistry C, 2025)
Gold patchy nanoparticles, anisotropic structures in which a thin gold patch partially coats a spherical, dielectric core, exhibit tunable optical resonances but often succumb to morphological changes over time. Here, we address this challenge by incorporating silver post-synthesis in a continuous-flow process that can adjust and preserve the plasmonic properties. Using a triple cascade T-mixer, our synthesis proceeds in three sequential steps: (1) seeding positively charged polystyrene cores with 3–6 nm gold nanocrystals, (2) growing gold patches under high-chloride conditions and with a large excess of the reducing agent ascorbic acid to promote dense lateral spreading of gold, and (3) adding silver nitrate only after the gold patches have fully formed. We show that silver incorporation occurs over at least 45 minutes, influenced by the residual reducing agent, the interplay between soluble silver chloride complexes, and the partial precipitation–redissolution of AgCl. By adjusting the relative amounts of gold and silver precursors, we independently tune patch dimensions, composition, and optical properties. High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) and energy-dispersive X-ray spectroscopy (STEM-EDX) confirm the spatial distribution of silver, including its enrichment at the patch surface and underside. Significantly, a silver mole fraction of 0.15 delivers long-term stability, where the patch shape remains constant and the localized surface plasmon resonance (LSPR) position does not shift over four months. Lower silver fractions fail to suppress gradual restructuring, while much higher silver contents lead to the dissolution of silver-rich regions and a red-shift in the LSPR. Overall, this post-synthetic approach to incorporating silver in gold patchy nanoparticles ensures both enhanced tunability and improved stability, paving the way for advanced photonic and sensing application